Occurrence of the Blue Button Porpita porpita (Linnaeus, 1758) in the Iskenderun Bay, Northeastern Mediterranean Coast of Turkey - Gürlek, Mevlüt (Array, 2020)
The blue button Porpita porpita (Linnaeus, 1758) was observed for the first time in July 2018 in the Iskenderun Bay, Northeastern Mediterranean coast of Turkey. This is the third record of this species for Turkish marine waters, while it is the first record for Iskenderun bay. The presence of P. porpita in the northeastern Mediterranean coast of Turkey shows its extension from northwestern Mediterranean coast (Antalya Bay) of Turkey.